High‐intensity focused ultrasound combined with hysteroscopic resection for the treatment of placenta accreta. (30th August 2017) - Ye, M; Yin, Z; Xue, M; Deng, X
Abstract : Objective: The aim of this study was to evaluate the safety and efficacy of a combination of high‐intensity focused ultrasound (HIFU) and hysteroscopic resection while treating placenta accreta (PA). Design: A retrospective study. Setting: A university teaching hospital in China. Methods: This study included 25 patients diagnosed with PA who underwent HIFU followed by hysteroscopic resection in our hospital between January 2014 and December 2015. All patients had completed follow‐up data. Treatment efficacy and safety were evaluated retrospectively. Main outcome measures: Placenta accreta could be removed with hysteroscopic resection after HIFU. Results: All patients received one session of HIFU ablation therapy. The median total HIFU treatment time was 18 minutes and the median exposure time was 600 seconds. During treatment, 23 lesions showed massive grey‐scale changes and two lesions modest grey‐scale change. Contrast‐enhanced ultrasound showed signs of reduced perfusion in all lesions. During treatment, all patients tolerated the HIFU procedure well and completed the treatment. All patients complained of mild lower abdominal and sacrococcygeal pain, with a pain score ranging from 1 to 4 points. Seven patients complained of a 'hot' skin sensation. No serious complications were encountered during or after the procedure. All patients received hysteroscopic operations with a median of 2 days after HIFU treatment. The average depth of the uterus was 10.36 ± 2.14 cm. The median volume of intraoperative blood loss was 20 ml, and no blood transfusions were given. Sixteen patients underwent only one session of hysteroscopic resection and nine patients underwent a second session of hysteroscopic resection operation 11–61 days after the first operation. All patients preserved their uterus and tolerated the hysteroscopic operation well. Of the 25 patients, two had uterine perforation during the first operation. No other severe hysteroscopic complication was observed. The average hospital stay was 8.4 ± 1.6 days. After treatment the median duration of vaginal bleeding was 10 days. Twenty‐one patients recovered normal menstruation 34 days after the operation. The other four patients continued breastfeeding and therefore exhibited abnormal menstruation. Conclusions: HIFU treatment followed by hysteroscopic resection is safe and effective in treating patients with PA. Tweetable abstract: For patients with placenta accreta, HIFU treatment before hysteroscopic resection could help reduce risk during the procedure of hysteroscopic resection. Tweetable abstract: For patients with placenta accreta, HIFU treatment before hysteroscopic resection could help reduce risk during the procedure of hysteroscopic resection.